Unveiling the Uncommon: Intrauterine Diagnosis of a Fetal Ovarian Cyst – A Rare Case Report and Review of the Literature - Leo Setyadi; Peby Maulina Lestari; Nuswil Bernolian; Putri Mirani; Abarham Martadiansyah (Media of Health Research, 2026)
Fetal Ovarian Cysts (FOCs) are a rare condition that can be detected through prenatal ultrasonography. This report discusses a case of a preterm primigravida with suspected FOCs, identified via ultrasound at 34 weeks of gestation. Conservative management with serial monitoring was implemented. Spontaneous delivery occurred at 36 weeks, resulting in a live birth, followed by postnatal monitoring. Fetal ovarian cysts result from hormonal stimulation, leading to abnormal follicular growth and fluid-filled cyst formation. Detection is primarily through prenatal ultrasound, with MRI aiding further evaluation. Management depends on cyst size and characteristics, with conservative monitoring for smaller cysts and intervention for larger or complicated cases. Most fetal ovarian cysts regress spontaneously postnatally, though persistent hormone levels may prolong their presence. Conservative management is often effective, with postnatal monitoring essential to prevent complications and unnecessary surgery. This case highlights the importance of early detection, close monitoring, and a multidisciplinary approach in managing FOCs.